Analisis Pengaruh Narrow Money (M1) Dan Broad Money (M2) Terhadap Laju Inflasi Di Indonesia - Siti Rahmi Utami; Rosita Suryaningsih (Ultima Accounting : Jurnal Ilmu Akuntansi, 2011)
The abjective of this study is to analyze the effect of narrow money and broad money on inflation rate in Indonesia. Those economic indicators are chosen as we expect the results of this study will be the reference in making the monetary policy. The data is the yearly data within 2003-2007, obtained from the annual report of Bank Indonesia. Data were analyzed using regression test. Independent variables used are narrow money and broad money, while the dependent variable is the rate of inflation in Indonesia. The result of our research shows that the narrow money has significantly negative effect on inflation rate, while broad money has significantly positive effect on inflation rate. Key Words : Narrow Money, Broad Money, and Inflation Rate